Antiviral activity of Bignoniaceae species occurring in the State of Minas Gerais (Brazil): part 1 - Brandao, G. C.; Kroon, E. G.; dos Santos, J. R.; Stehmann, J. R.; Lombardi, J. A. [UNESP]; de Oliveira, A. Braga (Wiley-Blackwell Publishing, Inc, 2010)
Aims:To evaluate the antiviral activity of Bignoniaceae species occurring in the state of Minas Gerais, Brazil.Methods and Results:Ethanol extracts of different anatomical parts of bignoniaceous plant species have been evaluated in vitro against human herpesvirus type 1 (HSV-1), vaccinia virus (VACV) and murine encephalomyocarditis virus (EMCV) by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. A total of 34 extracts from 18 plant species selected according to ethnopharmacological and taxonomic criteria were screened. Fifteen of the 34 extracts (44 center dot 1%) have disclosed antiviral activity against one or more of the viruses assayed with EC(50) values in the range of 23 center dot 2 +/- 2 center dot 5-422 center dot 7 +/- 10 center dot 9 mu g ml-1.Conclusions:Twelve of the 34 extracts (35 center dot 3%) might be considered promising sources of antiviral natural products, as they have shown EC(50) < 100 mu g ml-1. The present screening discloses the high potential of the Bignoniaceae family as source of antiviral agents.Significance and Impact of the Study:Active extracts were identified and deserve bioguided studies for the isolation of antiviral compounds and studies on mechanism of action.
Keywords: antiviral activity; Bignoniaceae; EMCV; HSV-1; in vitro assays; plant extracts; VACV